Designing and Implementing an In-Service Training Course for School Teams on Inclusive Education: Reflections from Participants - Tiina Kivirand; Äli Leijen; Liina Lepp; Tiiu Tammemäe (MDPI AG, 2021)
Significant and effective implementation of inclusive education (IE) has been a major challenge in many countries during the last decades. Although teachers' knowledge and skills are considered a key factor for successful inclusive practice, the whole school staff commitment and contribution to implementing IE policies are equally important. Collaboration between different professionals such as teachers, school leaders, and support specialists is crucial. This study aimed to design and implement an in-service training course for school teams (teachers, support specialists, school leaders) on IE in the Estonian context and to explore how participants experienced learning as a team in this course. The results of this study showed that the main aspects of the in-service training for school teams valued by participants were: (1) All topics covered in a systematic and coherent way gave a good opportunity to focus on relevant issues, which should be considered in the schools' self-development activities in the field of IE; (2) practical approach to training structure helped to identify priority areas that need to be developed in particular schools; (3) learning from each other both within their own school team and across school teams contributed to finding the best solutions for meaningful implementation of IE. The implication of these findings is further discussed in the paper.